Promoting vaccination: implementation of targeted interventions to enhance access to vaccination services in Quebec (Canada). Issue 12 (December 2015) - Dubé, E.; Gagnon, D.; Audet, D.; Bradet, R.; Boulianne, N.; Guay, M.; Sauvageau, C.
Highlights: Over the implementation period, prioritized interventions were implemented or strengthened in many vaccination clinics. However, status quo and abandon of recognized effective practices to increase vaccine uptake were also observed. The implementation of new practices in vaccination services takes time and requires the collaboration of all partners.